Psychomotor profile of autistic spectrum deficit children - BUSTO, Andressa Mayara de Lima; BRACCIALLI, Ligia Maria Presumido (Faculdade de Filosofia e Ciências, 2018)
The brain function changes that occur on the Autistic Spectrum Disorder are caused by a neurodevelopment disarrangement, that can causes communications deficits, motor skills and social relationship delays. Associated to cortical changes the motor experiences reduction prejudice the Autistic Spectrum Deficit Children executed movements quality and acquisition, that can interfere on their autonomy. The aim of this research was evaluate if Autistic Spectrum Deficit Children have motor skills development compatible with it is expected for children with normal development, and if there is a relation between the chronological age and the motor skill development level of this children. Were evaluated children from two to eleven years old with Autistic Spectrum Deficit diagnosis. The evaluation was based on the Motor Development Scale (MDS). To analyze the studied variables was used the Kolmogorov-Smirnov test for the normalization, and the T-Student test for the comparison of the numeric variables between general motor age (IMG) and chronological age (IC). For the test a 5% level of rejection of the null hypothesis was set. 14 Autistic Spectrum Deficit Children participate of the data gathering, with average age of 4,9 ± 1,6 years. The average general motor age (IMG) obtained was 35,7 months and the average chronological age (IC) was 66,7, being the general motor age average significantly lower than the chronological age. The was no significant statistic relevance in the EDM contemplated domains, but the domains are under the normative average established by EDM (89-80), highlighting the low language score of 18,9. The data showed that the evaluated children are under the normative average of the chronological motor development index, that occurs by a increase in the response latency time of the no Autistic Spectrum Deficit debilitating their motor sequencing, reducing the necessary motor adaptations. The light and moderated motor disturbances could go unnoticed by the society sectors that accompany Autistic Spectrum Deficit Children, so the treatment is postponed and only occurs in cases that the disturbances became serious and harms their school and social performance. Children diagnosed with Global Development Disorder show psychomotor performance lower than it is expected for their chronological age.